Upper Mantle P and S Wave Velocity Structure of the Kalahari Craton and Surrounding Proterozoic Terranes, Southern Africa. Issue 16 (23rd August 2019) - Ortiz, Kameron; Nyblade, Andrew; van der Meijde, Mark; Paulssen, Hanneke; Kwadiba, Motsamai; Ntibinyane, Onkgopotse; Durrheim, Raymond; Fadel, Islam; Homman, Kyle
Abstract: New broadband seismic data from Botswana and South Africa have been combined with existing data from the region to develop improved P and S wave velocity models for investigating the upper mantle structure of southern Africa. Higher craton‐like velocities are imaged beneath the Rehoboth Province and parts of the northern Okwa Terrane and the Magondi Belt, indicating that the northern edge of the greater Kalahari Craton lithosphere lies along the northern boundary of these terranes. Lower off‐craton velocities are imaged beneath the Damara‐Ghanzi‐Chobe Belt, and may in part reflect thinning of the lithosphere beneath the incipient Okavango Rift. Lower velocities are also imaged to the north and northwest of the Bushveld Complex beneath parts of the Okwa Terrane, Magondi Belt, and Limpopo Belt, indicating that cratonic upper mantle in some areas beneath these terranes may have been modified by the 2.05‐Ga Bushveld and/or 1.1‐Ga Umkondo magmatic events. Plain Language Summary: P and S waves travel times from large, distant earthquakes recorded on seismic stations in Botswana and South Africa have been combined with existing data from the region to construct velocity models of the upper mantle beneath southern Africa. The models show a region of higher velocities beneath the Rehoboth Province and parts of the northern Okwa Terrane and the Magondi Belt, which can be attributed to thicker cratonic lithosphere, and a region of lower velocities beneath the Damara‐Ghanzi‐Chobe Belt and Okavango Rift, which can be attributed a region of thinner off‐craton lithosphere. This finding suggests that the spatial extent of thick cratonic lithosphere in southern Africa is greater than previously known. In addition, within the cratonic lithosphere an area of lower velocities is imaged, revealing parts of the cratonic lithosphere that may have been modified by younger magmatic events. Key Points: Thick cratonic lithosphere extends beneath the Rehoboth Province and parts of the northern Okwa Terrane and Magondi Belt The northern edge of the greater Kalahari Craton lithosphere lies along the northern boundary of the Rehoboth Province and Magondi Belt Cratonic mantle lithosphere beneath the Okwa Terrane and Magondi Belt may have been chemically altered by Proterozoic magmatic events